Netizens' opinions on law enforcement and social responsibility - Hartanto (Indonesia Research and Study Center, 2023)
This research is to capture what the Indonesian Netizen considered and hoped (“Opinion”) regarding the law enforcement proceeding on the criminal case of kakao theft accused to Nenek Minah (Case Number 247/Pid.B/2009/PN.PWT). The Case of Nenek Minah is regarded as a case which harass the society’s sense of justice. The Indonesian Netizen considered that it is an irony and againts conscience to bring Nenek Minah to a legal proceeding just for stealing 3 pieces of kakao. The Indonesian Netizen compared the inequality between the level assertiveness of legal enforcement on the Case of Nenek Minah with corruption cases or cases concerning the sovereigns and the haves. The Indonesian Netizen hoped that the law would be more fair, humane and full of conscience instead. Keyword: law enforcement, criminal, netizen, Nenek Minah